Primary lesser sac myxoid liposarcoma: A case report - Noushad, S. Navin (Int J Surg Case Rep, 2016)
INTRODUCTION: Lesser sac pathological entities are uncommon. Most of these are tumors and are generally misdiagnosed as retroperitoneal lesions. CASE REPORT: A 62 year old male with past history of treated hypopharyngeal cancer presented with progressive abdominal distension. Physical examination revealed a midline intra abdominal mass in the epigastrium and umbilical region. Radiological investigations were suggestive of a retroperitoneal tumor,an image guided biopsy was reported as atypical lipoma. Surgical exploration confirmed a large multi lobulated tumor arising primarily from the lesser sac, post operative histopathological examination confirmed a myxoid liposarcoma. DISCUSSION: Primary lesser sac tumors are rare, a literature review of primary lesser sac tumors with particular reference to myxoid liposarcoma is presented. CONCLUSION: Primary lesser sac liposarcomas are rare neoplasms. The myxoid variant is unique for its peculiar biological behavior, in its sensitivity to chemotherapy and radiotherapy and for the presence of specific cytogenetic marker.